PENERAPAN TEKNOLOGI TOKO ONLINE UNTUK PEMASARAN PRODUK BAGI IBU-IBU AISYIYAH GUNUNG KIDUL - Gita Indah Budiarti; Murein Miksa Mardhia; Ahmad Azhari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2019)
Marketing and promotion are the most important things for product sales. Aisyiyah Gunung Kidul mothers (partners) have products, one of which is snacks from the mokaf. There needs to be innovation in marketing to increase partner sales. This activity aims to create an online shop for partners and then train partners to use it. The method used is training and evaluation. The results of this activity partners are able to use the website and application well. Partners who can upload their products by 63%. Partners are very enthusiastic about this training, and hope that there will be a follow-up to this activity.